Truck Appointment Systems: Where We Are and Where to Go from Here. Issue 1 (January 2016) - Huynh, Nathan; Smith, Daniel; Harder, Frank
Given their potential to improve drayage and terminal operations, truck appointment systems are needed more than ever to alleviate the growing truck drayage crisis at major U.S. ports. This paper examines the state of the art and the state of the practice for truck appointment systems, discusses their shortcomings, and identifies elements of successful and effective truck appointment systems. This paper aims to illuminate the intricacies of truck appointment systems, to discuss elements and features that need to be considered in actual or studied systems, and to highlight areas that need additional research.